Edible bird nest as a potential cognitive enhancer - Loh, Su-Peng; Cheng, Shi-Hui; Mohamed, Wael Mohamed Yousef (Frontiers Media S.A., 2022)
Cognitive enhancement is defined as the augmentation of the mind’s core capabilities through the improvement of internal or external information processing systems. Recently, the focus has shifted to the potential therapeutic effects of natural products in improving cognitive function. Edible bird’s nest (EBN) is a natural food substance derived from the saliva of swiftlets. Until today, EBN is regarded as a high-priced nutritious food with therapeutic effects. The effectiveness of dietary EBN supplementation to enhance brain development in mammals has been documented. Although the neuroprotection of EBN has been previously reported, however, the impact of EBN on learning and memory control and its potential as a cognitive enhancer drug remains unknown. Thus, this article aims to address the neuroprotective benefits of EBN and its potential effect as a cognitive enhancer. Notably, the current challenges and the future study direction in EBN have been demonstrated.